Pengaruh Gaya Hidup, Cita Rasa Dan Kepercayaan Merek Terhadap Minat Beli Jamu Suwegerr Ibu Mety di Kabupaten Sidoarjo - Muhammad Maullana Arifin; Ni Made Ida Pratiwi; Agung Pujianto (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
The tradition of consuming traditional herbal medicine has declined. This is due to the development of more modern beverages, so that these conditions slowly change people's perspective on traditional herbal medicine, resulting in a decline. However, after conducting a pre-survey to 30 respondents, it shows that most Indonesians still like traditional herbal medicine. Jamu Suwegerr brand is one of the traditional herbal medicine whose processing is carried out in Keboansikep Village, Sidoarjo Regency. The herbal brand is used by researchers to see whether people also like or are interested in Suwegerr traditional herbal medicine and analyze the factors that influence people's buying interest in Suwegerr traditional herbal medicine. This study aims to determine whether lifestyle, taste, brand trust have a positive and significant influence on buying interest in Suwegerr herbal medicine. The method used in this research is quantitative with a questionnaire instrument. The type of research used is associative, while the population in this study is the people in Gedangan and Sedati Districts and the sample used is 100 respondents using convenience sampling technique. The results of this study indicate that Lifestyle, Taste and Brand Trust have a positive and significant effect on buying interest in Jamu Suwegerr both partially and simultaneously. Recommendations for further researchers can develop this research again by conducting research on any factor of the variables that the researchers mentioned earlier and can use different samples and populations.